INTIMACIES AND DIGITAL MEDIA INFRASTRUCTURES - De Ridder, Sander; Dhaenens, Frederik; Duguay, Stefanie; Ferris, Lindsay; Paasonen, Susanna (AoIR Selected Papers of Internet Research, 2018)
The breadth of what it means to study intimacies in the context of media has changed significantly in recent years because of current technological, social, and cultural changes. The digital mediation of intimacy - the changing attitudes, experiences, and practices of intimacy performed through digital media - demands that scholars look beyond well-established frameworks for studying intimacy and media, expanding their methodological and theoretical perspectives in order to fully comprehend intimate lifeworlds and the digital. This panel aims to examine the various intimacies - understood here as a range of affects, practices and sociocultural arrangements - that take place through and are reconfigured by digital media infrastructures. In particular, it aims to explore how digital infrastructures and intimate arrangements are intertwined, thereby challenging the assumptions that digital media's reconfigurations of intimacy are associated with either positive or negative outcomes. Through analytical approaches that interrogate the material complexities of digital media in relation to individuals' intimate lifeworlds, this panel's papers uncover the nuances of digitally mediated intimacies. They identify the opportunities that digital media infrastructures facilitate for representation, social connection and sexual excitement while acknowledging infrastructural influences in the reinforcement, commodification, and marginalization of particular expressions of intimacy. Through textual analysis, in-depth interviews, ethnography, and close readings of a range of digital media, from messaging apps to video sharing platforms, these studies generate thick data that exposes the often unseen digital media infrastructures running underneath, through and in the background of intimacies.